Desain Penulisan Buku Ajar Bahasa Arab (Analisis Deskriptif Buku Al-‘Arābiyyah Baina Yadaik) - Muhammad Yusuf; Muhammad Ilham Akbar (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2018)
The strategic position of textbooks in Arabic learning is reflected in its role as a medium in transferring knowledge, ideology, and culture. Therefore giving attention to the primary principles in writing Arabic textbooks is a requirement. The realization of the socio-cultural, psychological, linguistic, and pedagogical basis in Arabic textbooks is not as easy as turning the palm. Many found writing designs that are "perfunctory" so that it has implications for the "infertility" of the strategic role of textbooks. This paper intends to examine Al-‘Arābiyyah Baina Yadaik book comprehensively. At least in the last two decades, this book exists in the treasury of Arabic education in Indonesia. Library research is the method used in this study. While an objective, systemic, and open framework is a procedure in analyzing problems. This study formulates that the design of al-‘Arābiyyah Baina Yadaik book is under the primary principles in writing Arabic textbooks, namely: a) socio-cultural: accommodating aspects of the culture of Arab society and Islam; b) psychological: following the intellectual abilities of learners, pay attention to individual differences, according to the level of language competence of learners, the integration of student books and teachers, and create orientation and norms for students; c) language: accommodating elements of language and language skills, the material is prepared using Arabic Fusha, paying attention to symbols; d) pedagogical: the material in al-‘Arābiyyah Baina Yadaik book has been prepared based on good selection, gradation, presentation and repetition criteria. Keywords: Al-‘Arābiyyah Baina Yadaik; Socio-cultural; Psychological; Linguistics; Pedagogical